Students with disabilities in general education settings: general education teacher preparation - Anderson, Mary Jo (Kansas State University, 2010)
Historically, the provision of special education has moved from settings isolated from children without disabilities to services in public school classrooms with non-disabled peers. As advocates began to impact civil rights legislation, the educational rights of individuals with disabilities were realized, and laws began to protect them. Public Law 94-142, 1975 and subsequent reauthorizations assured these students a free and appropriate public education and, to the greatest extent possible, with non-disabled peers. In 2002, the No Child Left Behind Act of 2001 became law. Its goal is that all children, including children with disabilities, attending public schools in the United States would be proficient in reading and mathematics by 2014. Consequently, students with disabilities have had an increased presence in general education classrooms. Some leaders in the field of special education imply that teacher preparation might not be keeping up with current trends and that it is their responsibility to make changes to teacher education programs so that beginning teachers are prepared for current job demands. The primary purpose of this study was to determine what is being taught in elementary education teacher preparation programs regarding how to teach students with disabilities who are educated entirely or in part in general education settings. The goal was to provide information to IHE’s considering more comprehensive and specialized training for elementary preservice general educators by making critical program adjustments in order to prepare effective educators in the context of classrooms in which students with disabilities receive some of their education, and importantly, to inform those adjustments. This study explored levels to which preferred knowledge and skills for including students with disabilities in elementary general education classrooms are taught and assessed. It also looked at differences among state licensing and university graduation coursework requirements. The study represented approximately 15,075 preservice teachers from 72 different universities in the United States. It revealed a full range of levels at which skills are taught and assessed. There are notable inconsistencies in special education requirements for general education teacher candidates seeking initial licensure.
Keywords: Teacher requirements for inclusion; Special education; Education, Teacher Training (0530)